Diversidade de vespas sociais (Hymenoptera, Vespidae) em diferentes fitofisionomias do Centro-Leste do Estado de São Paulo - Clemente, Mateus Aparecido [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Social wasps exhibit a considerable species abundance, they participated of food webs, and they can play a role in the biological control, in the monoculture and in the natural environment, they act as possible pollinators and frequent floral visitors, and the genus Polistes is considered a 'key' for the understand of evolution in the social behaviour. In 12 collects that were performed in each one of the five areas of study in the state of São Paulo, it was collected 31 species and 8 genera, which totalled 913 individuals. In this total, 81,16% belongs to the Epiponini tribe, 16,32% belongs to Mischocyttarini tribe and only 2,52% belongs to the Polistini tribe. The species more abundant were Agelaia pallipes (28 individuals, and frequency = 32,64%) and Agelaia vicina (210 individuals, frequency = 23,00%). In regarding to the influence of rainfall in the richness of the social wasps, only in the restored forest (t = 33,998 p = 0.002) and riparian forest (t = 22,583; p = 0.035) it occurred significant differences. For the relative humidity, there was no significant differences in any of the five areas. In regarding the variable environment temperature, there was only influence in the restored forest. For rainfall in regarding the abundance, there was a positive correlation in the restored forest, and a negative correlation in the ' Cerradão. However, regarding the temperature, there was a significance in relation to the abundance in the restored forest. For the Shannon-Wiener diversity index (H ') there was a greater value for restored forest (H' =1,991). It has obtained an abundance of 477 (52,25%) individuals by active search and 436 (47,75%) for attractive traps. For the richness, it was obtained 31 species, being 28 (90,32%) by active search and 23 (74,19%) by attractive traps; however, it was not observed differences between these methods for the abundance and richness. The genus more abundant was Agelaia with 30,88% in ...

Os vespídeos sociais apresentam uma considerável abundância de espécies, participam de teias alimentares, podem atuar no controle biológico em monoculturas e no ambiente natural, atuam como possíveis polinizadores e visitantes florais frequentes. Em seis coletas realizadas em meses alternados, para cada uma das cinco áreas deste estudo no Estado de São Paulo, coletou-se 31 espécies e oito gêneros, totalizando 913 indivíduos. Desse total 81,16% são pertencentes à tribo Epiponini, 16,32% pertencem à tribo Mischocyttarini e somente 2,52% à tribo Polistini. As espécies com maior abundância foram Agelaia pallipes (298 indivíduos, frequência = 32,64%) e Agelaia vicina (210 indivíduos, frequência = 23,00%). Em relação à influência da pluviosidade na riqueza de vespas sociais, apenas na Mata Restaurada (t = 33.998 p = 0,002) e na Mata Ciliar (t = 22,583; p = 0,035) ocorreram diferenças significativas. Para a umidade relativa do ar não houve diferença significativa em nenhuma das cinco áreas. Na variável ambiental temperatura houve influência apenas na Mata Restaurada. Para pluviosidade em relação à abundância, houve uma correlação positiva na Mata Restaurada e uma negativa no Cerradão. Porém, para a temperatura, houve significância em relação à abundância na Mata Restaurada. Para o índice de diversidade de Shannon-Wiener (H') obteve-se maior valor para a Mata Restaurada (H'= 1,991). Obtivemos uma abundância de 477 (52,25%) indivíduos por busca ativa e 436 (47,75%) para armadilhas atrativas. Para riqueza, foram 31 espécies, sendo 28 (90,32%) por busca ativa e 23 (74,19%) para armadilhas atrativas, no entanto não observamos diferenças entre os métodos para a abundância e riqueza. O gênero mais abundante foi Agelaia com 30,88% nas armadilhas atrativas e 28,47% na busca ativa. Não se contatou diferença significativa entre os métodos de busca ativa e armadilhas atrativas para amostrar a riqueza de...
Keywords: Wasps; Vespa; Entomologia; Incendios; São Paulo (Estado)